Artwork Copyright Legal Protection on Non-Fungible Tokens (NFT) - Tuhana, Tuhana; Kharisma, Dona Budi; Khoirunnisa, Nabilah (Faculty of Law, Universitas Pekalongan, 2024)
The purpose of this legal research is to find out the legal problems in protecting the copyrights of creators of works of art on Non-Fungible Tokens (NFT) and to find out the forms of legal protection for creators’ copyrights of works of art on NFT. The type of research is normative legal research. The approaches used are statute approaches, conceptual approaches, and comparative approaches. The legal materials used are all regulations regarding copyright that exist in Indonesia and The United States of America (USA). NFT is a copyright protection solution for creators of works of art in the digital era. Indonesia does not yet have a digital copyright act while the USA has a digital copyright act called the Digital Millennium Copyrights Act (DMCA) which is able to protect the copyrights of art creators in NFT. In Indonesia, it has not yet been regulated regarding the prohibition of the importation of anti-circumvention devices, which has been handled in Chapter 1201 of the DMCA. Then there is also no regulation regarding the deletion of NFT content, which indicates violations in Indonesia, which has been regulated in USA.